FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PERBANKAN SYARIAH: (SEBUAH TINJAUAN LITERATUR) - RINA EL MAZA; YENTI AFRIDA; RAHMI FAHMI; LAURA SYAHRUL (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This article examines the future research direction of Islamic banking SDI through literature review. The main purpose of this article is to map previous research related to factors that affect the performance of Islamic banking employees, especially Banking employees whose conventional banks have previously turned into Islamic banks. Literature review is carried out by collecting writings that have been published in reputable journals. The method used in this study was to use the Harzing publish or Perish application as well as mandeley. The keyword